CHANGES IN THE PARAMETERS OF 24-HOUR BLOOD PRESSURE MONITORING AND ARTERIAL STIFFNESS IN PATIENTS WITH HYPERTENSION AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE TREATED WITH VALSARTAN - N. A. Karoli; G. R. Dolishnya; A. P. Rebrov (Столичная издательская компания, 2015)
Aim. To study changes in the parameters of the 24-hour blood pressure (BP) monitoring and arterial stiffness (AS) in patients with arterial hypertension (HT) and chronic obstructive pulmonary disease (COPD) treated with angiotensin II receptors blocker, valsartan. Material and methods. Men with HT and COPD (n=23), who have been receiving valsartan with starting dose 80 mg/day for 6 months as antihypertensive therapy were included into the study. If target BP was not achieved, correction of the valsartan dose was carried out with the hydrochlorothiazide addition when needed. Clinical examination, 24-hour BP and AS monitoring using BPLab MnSDP-2 monitor ("Petr TELEGIN",Russia), clinical evaluation of COPD were performed. Results. Abnormal circadian BP profile and the elastic properties of arteries were diagnosed in the majority of hypertensive patients with COPD. Valsartan therapy allowed to achieve target BP levels in 100% of patients, normalization of circadian BP profile in 56.5%, improvement in AS parameters: a significant increase in PTT2 (from 89.6±14.3 to 94.4±18.4 ms), reduction of (dP/dt)max (from 566.6±117.9 to 518.8±146.2 mmHg/s), AIx (from -4.0±15.2 to -11.6±20.8 %) as compared to the baseline. Circadian changes in daily parameters of AS in studied patients with the most obvious night-time abnormalities of the elastic properties of arteries were detected. Valsartan intake led to Alx reduction at night-time. Conclusion. Valsartan-based therapy in hypertensive patients with concomitant COPD demonstrated a high antihypertensive efficacy and favorable changes in the elastic properties of the vascular wall that confirm its organoprotective effect.